From road infrastructure to urban space. Transforming Via Flaminia into a new cultural axis of Rome (Gaceta Técnica, 2017)
The street is the outside space that shapes our daily life. Its study means to understand the most important public space of the city. The research project described herein attempts to understand how the street becomes an urban space -a livable space-, its importance as a social realm and the design elements that make it a successful space in the city. The scope of the research goes from a general overview of the street to the study of the specific case represented by Via Flaminia, one of the most important historical axes of Rome. The approach to the research is divided into two parts; first a theoretical, historical and referential investigation; and a second part that includes a focused analysis of Via Flaminia and concludes with the application of this analysis to the design of an urban and an architectural project for this chosen street. The proposed project seeks to solve the limited permeability of the street and attempts to provide continuity to its image. It explores the repurposing the existing building typologies with new social, cultural and recreational functions. One of the main goals is to transform this street into a revitalized cultural node of the city, to transform Via Flaminia from a road infrastructure to a quality urban space of the City of Rome, seeking that it becomes the new cultural axis of the city. The architectural project focuses on a critical point of the street, developing a Cultural and Educational Center.
Keywords: cultural axis; Via Flaminia; Rome